Vizualizacija prostorskih medicinskih podatkov na osebnem računalniku - Podgorelec, David (Informatica Medica Slovenica, 2002)
We present an algorithm for volume rendering that is simple and sufficiently fast to be run on a low-cost personal computer. The algorithm supports the visualization of large data sets, which are typically examined in medical applications. The algorithm is based on a secondary model called the list of visible voxels. Visualisation is accelerated by eliminating voxels not interesting to a user. These so-called white voxels present air, objectsć interior and parts of objectsć boundaries hidden from the userćs viewpoint. In the last part of the paper, some practical examples from the medical data sets are considered.
Keywords: computer graphics; izdelava modelov; medical data sets; prostorski podatki; računalniška grafika; senčenje prostorskih podatkov; visualisation; vizualizacija medicinskih podatkov; vizualizacija prostorskih podatkov; voksli; volume data; volume data visualisation; volume rendering; voxels; znanstvena vizualizacija